2019
DOI: 10.1080/00273171.2019.1608799
|View full text |Cite
|
Sign up to set email alerts
|

Testing Measurement Invariance with Ordinal Missing Data: A Comparison of Estimators and Missing Data Techniques

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 33 publications
2
48
0
9
Order By: Relevance
“…This could also explain why the type I error rates from rFIML were conservative. Similar findings have been reported in previous research (e.g., Chen et al, 2019). Fourth, rFIML showed higher perfect recovery rates and power than WLSMV_PD in detecting non-uniform noninvariance (i.e., directions of non-invariance are different across non-invariant items) when missing data present.…”
Section: Major Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…This could also explain why the type I error rates from rFIML were conservative. Similar findings have been reported in previous research (e.g., Chen et al, 2019). Fourth, rFIML showed higher perfect recovery rates and power than WLSMV_PD in detecting non-uniform noninvariance (i.e., directions of non-invariance are different across non-invariant items) when missing data present.…”
Section: Major Findingssupporting
confidence: 89%
“…These methods include full information maximum likelihood (FIML), robust full information maximum likelihood (rFIML), and the mean and variance adjusted weighted least-squared method paired with pairwise deletion (WLSMV_PD) (e.g., Beam, Marcus, Turkheimer & Emery, 2018;Bou Malham & Saucier, 2014;Fokkema, Smits, Kelderman, & Cuijpers, 2013;Sommer, et al, 2019). Given that previous research has shown that rFIML outperformed FIML for ordinal data (e.g., Chen, Wu, Garnier-Villarreal, Kite & Jia, 2019), we only consider rFIML and WLSMV_PD in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…In factor analysis, the investigation of measurement invariance (Millsap, 2011) is heavily discussed. It has been recommended that invariance analysis for ordinal variables should also treat variables as ordinal (Chen et al, 2020;Svetina et al, 2020). By continuing our arguments, we think that the assessment of invariance can be equally defended by treating ordinal variables as continuous.…”
Section: Discussionmentioning
confidence: 67%
“…In the modeling of factor structures, the investigation of measurement invariance (Millsap, 2011) is heavily discussed. It has been recommended that invariance analysis for ordinal variables should also treat variables as ordinal (Chen, Wu, Garnier-Villarreal, Kite, & Jia, 2020). By continuing our arguments, we think that the assessment of invariance can be equally defended by treating ordinal variables as continuous.…”
Section: Discussionmentioning
confidence: 70%